Oxygen Reduction Reaction Activity of Microwave Mediated Solvothermal Synthesized CeO2/g-C3N4 Nanocomposite - Soren, Siba; Hota, Ipsha; Debnath, A. K.; Aswal, D. K.; Varadwaj, K. S. K.; Parhi, Purnendu (Frontiers in Chemistry, 2019)
Electrocatalytic active species like transition metal oxides have been widely combined with carbon based nanomaterials for enhanced Oxygen Reduction Reaction (ORR) studies because of the synergistic effect arising between different components. The aim of the present study is to synthesize CeO2/g-C3N4 system and compare the ORR activity with bare CeO2. Ceria (CeO2) embedded on g-C3N4 nanocomposite was synthesized by a single step microwave mediated solvothermal method. This cerium oxide based nanocomposite displays enhanced ORR activity and electrochemical stability as compared to bare ceria.